THE BULGARIAN NATURAL AND CULTURAL HERITAGE UNDER THE AEGIS OF UNESCO. ORGANIZATION AND FUNCTIONALITY - Penerliev, Milen; Petkov, Veselin (Revista Inclusiones, 2021)
The paper examines the functional and hierarchical structure of the sites under the aegis of UNESCO in Bulgaria and categorizes them by individual lists according to the genesis, development and functioning of each site. The emphasis is placed on the sites which are part of the list of the world (natural and cultural) heritage of “outstanding universal value”. An in-depth analysis of the selected sites has been made in terms of geographic location and interaction with the specific area of their location. The sites have also been analyzed in terms of tourism and attendance, as well as trends in their development as tourist destinations. Finally, the paper focuses on the opportunities for increasing the tourism attractiveness of certain UNESCO World Heritage sites in Bulgaria.